2004
DOI: 10.1016/j.orthres.2004.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Production of consistent crush lesions in murine quadriceps muscle—A biomechanical, histomorphological and immunohistochemical study

Abstract: Poor healing of high-energy fractures is often associated with severe muscle damage. This mdy be partly due to the production, by the injured muscle, of inflammatory cytokines that somehow misdirect bone healing. In order to investigate this question, an animal model was established which embodies a controlled degree of muscle injury with a dose response to the energy absorbed, that can be characterised histologically. Using a custom crush jig, 60 CFLP mice had either 100 or 200 g masses dropped from a fixed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…Although IL-6 is classified as a pro-inflammatory cytokine it has a variety of biological functions. IL-6 can also act as in anti-inflammatory manner to inhibit the inflammatory response (Bunn et al, 2004;Xing et al, 1998). The expression of IL-6 mRNA was detected in different injury models of muscle regeneration Sheriff et al, 2009;Warren et al, 2002).…”
Section: Muscle Injury and The Degenerative Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Although IL-6 is classified as a pro-inflammatory cytokine it has a variety of biological functions. IL-6 can also act as in anti-inflammatory manner to inhibit the inflammatory response (Bunn et al, 2004;Xing et al, 1998). The expression of IL-6 mRNA was detected in different injury models of muscle regeneration Sheriff et al, 2009;Warren et al, 2002).…”
Section: Muscle Injury and The Degenerative Phasementioning
confidence: 99%
“…The expression of IL-6 mRNA was detected in different injury models of muscle regeneration Sheriff et al, 2009;Warren et al, 2002). For example, Bunn et al (2004) investigated the increase of IL-6 during regeneration following crush injury in rat muscle at different time points: 2, 4, 8, 16, and 24 days. The results showed a high level increase on day 2 post injury, decrease on day 4 and then increase again on day 8.…”
Section: Muscle Injury and The Degenerative Phasementioning
confidence: 99%
“…Among them, open crush injuries allow standardized evaluation of regeneration in a selected muscle (Schultz et al 1985, Rushton et al 1997). For the execution of the trauma, either forceps (McGeachie and Grounds 1987, Kurek et al 1997, Fink et al 2003) or custom-made devices have been used (Jarvinen and Sorvari 1975, Rushton et al 1997, Bunn et al 2004). …”
mentioning
confidence: 99%
“…Histological analysis of the regenerative process after crush injury has been done by a number of authors, describing the initial phase of inflammation followed by satellite cell activation, myotube regeneration, and fibrosis of the muscle (Jarvinen and Sorvari 1975, Schmalbruch 1976, Sorokin et al 2000, Bunn et al 2004). It has been shown that the development of fibrotic tissue is one of the key factors for regenerative deficits of muscle function after trauma (Anderson et al 1999, Nozaki et al 2008).…”
mentioning
confidence: 99%
“…Furthermore, changes in cytokine levels are dependent on the degree of injury. An experimental study demonstrated that more severe injury to muscles produced increased cytokine production and a greater degree of inflammation [27]. Clinical studies usually measure the changes of the cytokine levels to evaluate the surgical invasions [28, 29].…”
Section: Discussionmentioning
confidence: 99%